COVID-19 Ayurveda treatment protocol of governments of Nepal and India: a review and perspective - Pandit, Ram Deo; Singh, Rakesh Kumar (Applied Science and Technology Annals, 2020)
SARS-CoV-2 originated in Wuhan city of China in Dec 2019, was named COVID-19 and declared pandemic by WHO. Conventional system of medicine is seen proving ineffective in its treatment. The first case of COVID-19 was confirmed on 23rd January 2020 in Nepal and on 30th January 2020 in India. SARS, MERS and COVID-19 in China were effectively managed through Traditional System of Medicine (TSM). Glycyrrhizin like active component of medicinal herbs potentially inhibit virus replication and bear antiviral property. Government of Nepal and India released a treatment protocol for COVID-19. Protocols have taken COVID-19 on the basis of Dosha, Dhatu, Mala, etc. The symptoms of COVID-19 resemble Kapha-Vata-Samasargaj-Jawara with Pitta association (i.e. Sannipataj-Jawara). For foreign etiology of COVID-19 Ayurveda considers it Rakshayadi-Prakopa-Janya-Janapado-udhamsha and deployed management accordingly. Good immunity is important factor for arresting or preventing the disease, which can be achieved by regular administration of Rasayanas. The physician should not treat any COVID-19 infected patient without safety precautions or without informing the local authorities. Clinical researches on individual and poly herbal drugs in the protocol should be taken into series of clinical trials to test its effectiveness against COVID-19 and discover the pharmacology and prove its effectiveness and establish it among global scientific community.